The Case for Accrual Recording in the IMF's Government Finance Statistics System - Efford, Don (IMF Working Papers; Working Paper ;, 1996)
This paper investigates whether the planned revision of the IMF's A Manual on Government Finance Statistics should advocate an accrual basis of recording over the essentially cash basis of recording in the previous manual. The paper concludes that the revised manual should advocate an accrual basis in order to address deficiencies of the existing modified cash basis and enable a greater degree of harmonization with other macroeconomic statistical systems. The paper suggests a strategy that would enable countries to move progressively to compiling an extensive range of accrual information reconciling data on economic and financial flows and stocks.